(In)Significance of Financial Indicators as Stock Price Determinants- The Role of Value-Oriented Vs. Traditional Kpis in the Context of Shareholder Return (International Journal of Applied Research in Management and Economics, 2021)
As comprehensively discussed by prominent authors such as Fama or Schiller, stock return research is ever since its origin of major importance for the academic and business community given that decision-relevant information is analyzed and discussed, which can be used for investment decisions, to guide and improve corporate performance, to upgrade accounting standards, and disclosure requirements. In summary, partly inconclusive results of the past, the faster-changing environment, and the focus on the pharmaceutical industry motivate further research regarding the subject of stock return analysis.In this regard, this paper provides empirical evidence to the question of which financial indicators are significantly related to stock returns. First, it was theoretically argued that a meaningful indicator of operating and strategic performance should be highly associated with stock returns, given that management decisions that change shareholder wealth should simultaneously cause corresponding stock returns. Based on this assumption, this research analyzed several traditional indicators and EVA (as reported by Bloomberg). Second, the relationship between these financial determinants and stock returns was studied using the data of 29 pharmaceutical companies in a five-year period. Given the dataset's characteristics, a panel regression was the most appropriate method to enlighten the questions of interest. Finally, as a result of this study, empirical evidence shows that several financial indicators such as Equity PS, Turnover PS, or Cash PS are helpful to explain shareholder wealth but only to a very limited extend. Nevertheless, as outlined in the course of this paper, in terms of management control, the advantage of value-oriented indicators should not be denied, as this may contribute to less budgetary slack and better incentive systems.